2014
DOI: 10.1111/apha.12424
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of electrical activity in uterine muscle during pregnancy: a review

Abstract: The uterine muscle (the myometrium) plays its most evident role during pregnancy, when quiescence is required for adequate nourishment and development of the foetus, and during labour, when forceful contractions are needed to expel the foetus and the other products of conception. The myometrium is composed of smooth muscle cells. Contraction is initiated by the spontaneous generation of electrical activity at the cell level in the form of action potentials. The mechanisms underlying uterine quiescence during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 80 publications
0
74
1
Order By: Relevance
“…The search for the site and behavior of the pacemaker in the pregnant uterus has a long history (18,30,42). Several authors have suggested that the fundus of the uterus was the main origin of these contractions (2,3,8).…”
Section: Discussionmentioning
confidence: 99%
“…The search for the site and behavior of the pacemaker in the pregnant uterus has a long history (18,30,42). Several authors have suggested that the fundus of the uterus was the main origin of these contractions (2,3,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a significant doubt that myometrial action potentials travel in straight paths. In sheep (Parkington et al 1988), rodent ( Lammers et al 2008), and human (Mikkelsen et al 2013, Rabotti & Mischi 2015 action potentials are not found to travel linearly. The highest resolution electrical mapping of myometrium is in the guinea pig, which reveals that action potentials diverge and loop through tortuous paths, self-terminate, and usually do not propagate more than a few centimeters (Lammers et al 2008) (Fig.…”
Section: Problems With Action Potential Propagation As a Mechanism Fomentioning
confidence: 91%
“…Assuming the starting point is on the front wall, travel to the back wall is a distance of about 40 cm. Thus, speeds greater than 2 cm/s would be sufficient to accomplish this, and these values are routinely observed in human (Rabotti et al 2010, Rabotti & Mischi 2015 and rodent (Lammers 2013). However, there is a significant doubt that myometrial action potentials travel in straight paths.…”
Section: Problems With Action Potential Propagation As a Mechanism Fomentioning
confidence: 95%
See 2 more Smart Citations